ІСТОРІОГРАФІЯ ПЕРШОЇ ХВИЛІ УКРАЇНСЬКОЇ ЕМІГРАЦІЇ В КАНАДІ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the historiography analysis of literature in which the most important aspects of the first wave of the Ukrainian emigration in Canada of the late XIX-th century and the early XX-th century are represented. The issues published in Canada and in Ukraine before gaining the state independence were analyzed